Effect of carbohydrate restriction on body weight in overweight and obese adults: a systematic review and dose–response meta-analysis of 110 randomized controlled trials - Soltani, Sepideh; Jayedi, Ahmad; Abdollahi, Shima; Vasmehjani, Azam Ahmadi; Meshkini, Fatemeh; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2023)
Carbohydrate-restricted diets are one the most effective dietary interventions for weight loss. However, the optimum carbohydrate intake for implementing the most effective weight loss interventions is still being discussed. We aimed to determine the optimum carbohydrate intake for short- and long-term weight loss in adults with overweight and obesity. We searched PubMed, Scopus, Web of Science, and CENTRAL from inception to May 2021 for randomized controlled trials examining the effect of a carbohydrate-restricted diet (≤45% of energy intake) as compared to a control diet (carbohydrate intake >45% of energy intake) on body weight in adults with overweight/obesity. A random-effects dose-response meta-analysis was conducted to calculate mean difference for each %10 decrease in carbohydrate intake at 6-month, 12-month, and longer than 12 months follow-ups. The shape of the dose-dependent effects was also evaluated. The certainty of evidence was rated using the GRADE approach. The minimal clinically important difference (MCID) threshold was defined as 5% weight loss (equal to 4.39 kg). 110 trials were selected for the present meta-analysis. In the linear dose-response meta-analysis, each 10% decrease in carbohydrate intake reduced body weight by 0.64 kg (95% CI: -0.79 to -0.49; n=101 trials with 4135 participants, high-certainty evidence) at 6-month, and by 1.15 kg (95% CI: -1.61 to -0.69; 42 trials with 2657 participants, moderate-certainty evidence) at 12-month. Nonlinear dose-response meta-analyses indicated a monotonic reduction in body weight with the decrease in carbohydrate intake, with the greatest reduction at 5% at 6-month (mean difference 5%: -3.96 kg, 95% CI: -4.92 to -3.00) and at 10% at 12-month (mean difference 10%: -6.26 kg, 95% CI: -10.42 to -2.10). At follow-up longer than 12 months, dose-response analyses suggested a nonlinear effect, wherein carbohydrate intakes higher than 40% and lower than 30% were not effective for weight loss. Carbohydrate restriction is an effective dietary strategy for important weight loss in adults with overweight and/or obesity. At 6-month and 12-month follow-ups, body weight decreased proportionally, larger than the MCID threshold, along with the decrease in carbohydrate intake. At follow-up longer than 12 months, there was a nonlinear effect, with the greatest reduction at 30% carbohydrate intake.